Inhaled therapies for chronic obstructive pulmonary disease: a systematic review and meta-analysis - Jennifer K Quint; Eleanor L Axson; Adam Lewis; James Potts; Helene Vioix; Marie Pang; Scott Dickinson (BMJ Open)
Objectives To integrate evidence from randomised controlled trials (RCTs) and observational studies on the efficacy of inhaled treatments for chronic obstructive pulmonary disease using network meta-analyses.Methods Systematic searches MEDLINE and Embase based on predetermined criteria. Network meta-analyses of RCTs investigated efficacy on exacerbations (long-term: ≥20 weeks of treatment; short-term: <20 weeks), lung function (≥12 weeks), health-related quality of life, mortality and adverse events. Qualitative comparisons of efficacies between RCTs and observational studies.Results 212 RCTs and 19 observational studies were included. Compared with combined long-acting beta-adrenoceptor agonists and long-acting muscarinic antagonists (LABA+LAMA), triple therapy (LABA+LAMA+inhaled corticosteroid) was significantly more effective at reducing exacerbations (long-term 0.85 (95% CI: 0.78 to 0.94; short-term 0.67 (95% CI: 0.49 to 0.92)) and mortality (0.72 (95% CI: 0.59 to 0.89)) but was also associated with increased pneumonia (1.35 (95% CI: 1.10 to 1.67)). No differences in lung function (0.02 (95% CI: −0.10 to 0.14)), health-related quality of life (−1.12 (95% CI: −3.83 to 1.59)) or other adverse events (1.02 (95% CI: 0.96 to 1.08)) were found. Most of the observational evidence trended in the same direction as pooled RCT data.Conclusion Further evidence, especially pragmatic trials, are needed to fully understand the characteristics of patient subgroups who may benefit from triple therapy and for those whom the extra risk of adverse events, such as pneumonia, may outweigh any benefits.PROSPERO registration number CRD42018088013.